Pengaruh Intensitas dan Tujuan Penggunaan Media Sosial terhadap Produktivitas Belajar Mahasiswa Universitas Negeri Makassar dan Universitas Hasanudin - Hasdiansa, Ilma Wulansari (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study uses a quantitative research approach because it aims to measure the relationship between two variables, namely variable (X1) intensity of use, (X2) purpose of use and (Y) learning productivity. The population in this study were active students of Makassar State University and Hasanuddin University in the 2023-2024 academic year with a total population of 75554 and 100 samples. The data analysis method used in this study was validity and reliability testing. Followed by multiple correlation tests, hypotheses (t-test), and multiple linear regression. The results of the multiple correlation test showed that there was a significant relationship between variables (X1 and X2) to variable (Y) simultaneously as shown by the sig. F Change value of 0.011 <0.05. Furthermore, the hypothesis test (t-test) X1 has a sig value of 0.004 < 0.05 and X2 has a value of 0.013 < 0.05, both of which have an influence on variable Y. A linear regression test is used to determine the direction and magnitude of the influence of the independent variables (X1 and X2) on the dependent variable (Y), with X1 having a positive value of 0.379 and X2 having a negative value of -0.274.